2022
DOI: 10.3390/su14020815
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of the Technology Acceptance Model and Value-Based Adoption Model to Study the Adoption of E-Learning: The Moderating Role of e-WOM

Abstract: The Technology Acceptance Model (TAM) has lately been utilized in a number of studies to investigate why people reject or adopt new technologies like mobile commerce or e-learning. However, several studies have found weaknesses in TAM’s ability to predict consumers’ purchase intention behavior. To compensate for TAM’s weaknesses, this study presents a model that integrates all of TAM’s components with the Value-Based Adoption Model (VAM). The perceived benefits and sacrifices were considered to provide a list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 86 publications
(103 reference statements)
1
22
0
1
Order By: Relevance
“…Second, the research findings indicated that purchase price perceptions did not have a significant negative influence on the players' satisfaction and purchase intentions, thus H3 and H4 were rejected, which is in alignment with the finding of adopting e-learning [44]. If the value consumers gain from a product or service is higher than the cost they pay, purchase intention will be formed.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Second, the research findings indicated that purchase price perceptions did not have a significant negative influence on the players' satisfaction and purchase intentions, thus H3 and H4 were rejected, which is in alignment with the finding of adopting e-learning [44]. If the value consumers gain from a product or service is higher than the cost they pay, purchase intention will be formed.…”
Section: Discussionsupporting
confidence: 58%
“…If the value is lower, users will reject this product or service. In the context of e-learning, when learners are truly glad to learn using a system, they are willing to trade costs to obtain a better learning performance [44]. Similarly, if game players truly like traditional costume skins, they are willing to pay for a better game experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, many companies have started to pay attention to and re-examine their corporate policies from a consumer perspective to improve their strategic competition (Chen et al, 2012 ). Therefore, e-WOM has gradually attracted the attention of the institutions that develop online courses (Shehzadi et al, 2020 ; Liao et al, 2022 ).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%